The milpa, from Mesoamerica to present days, a multicropping traditional agricultural system serving agroecology - Vazeux-Blumental, Noa; Manicacci, Domenica; Tenaillon, Maud (Comptes Rendus Biologies)
The association of maize (Zea mays ssp. mays), common bean (Phaseolus vulgaris), and squash (Cucurbita ssp.) within the milpa represents the most emblematic multi-cropping subsistence system of Mesoamerica. This system was likely established in the Guerrero-Jalisco area in southwestern Central Mexico shortly after—or perhaps even before—the domestication of the three taxa. Its success relies on several factors: complementarity of nutritional intakes, resilience to biotic and abiotic constraints, and the mobilization of positive interactions between the three taxa, enabling the system to be productive under input-limited conditions. Higher yields compared to sole-cropping have frequently been described and attributed to the complementarity between the aerial and root systems of the different taxa of the milpa, as well as to direct and indirect facilitation processes involving root exudates, bacterial symbioses, and the mycorrhizal network. In Europe, while practiced until recently, the milpa has gradually been abandoned in favor of maize sole-cropping, except in some isolated regions (such as Transylvania) where this traditional agricultural system has persisted. The question of whether varieties of the three taxa used in multi-cropping systems were co-introduced to Europe at the time of the discovery of the Americas, as opposed to being re-associated later in Europe, remains open. It is important to note that maize usage differed: maize of flint type is coarsely ground for the preparation of polenta in Europe, while in Mesoamerica, tropical varieties are soaked in alkaline solution to improve nutritional quality before being finely ground to make tortilla dough. Recently, maize-bean intercropping has been reintroduced into modern European agricultural systems. However, the use of elite varieties and chemical inputs in conventional conducts prevents full exploitation of positive interactions between species. We argue here that milpa has an important role to play in the agroecological transition. In this context, we propose avenues for the selection of varieties that promote synergies between species and discuss the constraints linked to its mechanization.